FINANCIAL PATHWAYS LINKING GREEN LENDING TO CORPORATE VALUATION - Putu Amanda Setiawani; Henny Rahyuda (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The expansion of sustainable finance has increased attention to green lending as a mechanism for promoting environmental objectives while strengthening corporate value. Despite its growing adoption, evidence regarding the value implications of green lending remains inconclusive, particularly within emerging banking markets. This study evaluates the contribution of green lending to corporate valuation and examines whether credit risk and profitability function as financial pathways through which such effects may occur. The analysis is based on panel data from four Indonesian KBMI 4 banks covering the period 2015–2024. Green lending is measured using the Green Lending Ratio, corporate valuation is proxied by Tobin’s Q, credit risk is represented by the Non-Performing Loan ratio, and profitability is measured by Return on Assets. A path analysis approach employing panel regression with bank-clustered robust standard errors is applied. The results reveal that green lending contributes positively to corporate valuation. Credit risk exhibits a negative association with valuation, whereas profitability demonstrates a positive relationship. However, neither credit risk nor profitability significantly transmits the effect of green lending on valuation. These findings suggest that capital markets reward sustainability-oriented lending initiatives, while corporate valuation continues to depend largely on financial performance and asset quality.